2014
DOI: 10.1177/2165143414528241
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Investigation Into Family Perspectives After the Family Employment Awareness Training

Abstract: Competitive employment (i.e., employment in community settings among people without disabilities for minimum wage or higher) improves quality of life for people with disabilities who have individualized support needs (ISN). However, attaining competitive employment can be challenging for people with ISN. This study used a mixed methods design to evaluate the perspectives of 68 families who attended the Family Employment Awareness Training (FEAT). Findings indicated that families who attended FEAT (a) accessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In summary, the results of this study are consistent with research substantiating best practices in transition services [2,5,37,38]. Specifically, preparation for employment, family involvement, social skills training, daily living skills training, and community and agency collaboration were all emphasized as key elements of effective transition service programming.…”
Section: Theme Two: Key Objectives Of Transition Servicessupporting
confidence: 85%
“…In summary, the results of this study are consistent with research substantiating best practices in transition services [2,5,37,38]. Specifically, preparation for employment, family involvement, social skills training, daily living skills training, and community and agency collaboration were all emphasized as key elements of effective transition service programming.…”
Section: Theme Two: Key Objectives Of Transition Servicessupporting
confidence: 85%
“…Francis, Gross, Turnbull, and Parent-Johnson (2013) found that parent training on competitive employment options for people with disabilities through the Family Empowerment Awareness Training (FEAT) increased parent expectations for competitive employment. A follow-up survey found that parents reported accessing competitive employment resources following the trainings with nearly one fifth reporting competitive employment outcomes for their son or daughter (Francis, Gross, Turnbull, & Turnbull, 2014).…”
Section: Models For Parent Involvementmentioning
confidence: 99%
“…For many people with disabilities and other significant life barriers, their support systems tend to be overly represented by "paid supporters" and underrepresented by volunteer supporters and friends (Amado, 2013;Francis, Gross, Turnbull, & Turnbull, 2015;Hochman, Carter, Bottema-Beutel, Harvey, & Gustafson, 2015). This may primarily be due to society's tendency to shelter, protect, "take care of" and, intentionally or inadvertently, isolate people with disabilities.…”
Section: Community and Championsmentioning
confidence: 99%